School inclusion of deaf students in the Federal School System: context and challenges (Revista Educação, Artes e Inclusão, 2023)
This article aims to describe how the school inclusion of people with disabilities (focusing on the deaf student) has occurred in the Federal Education Network, in view of the legal and historical context of educational legislation and its consequences in regular and professionals. In this sense, the methodological itinerary used in the development of this work went the way of bibliographical research. To this end it brings an initial discussion on the development of inclusive policies in the network, highlighting projects, schedules and actions developed. It contextualizes High School Technical Vocational Education (EPTNM) in view of the legal and practical peculiarities for the inclusion of the deaf student. It reflects on the challenges that the Federal Institutions of Education have for a process of inclusion of the real and successful deaf student, taking into consideration internal pedagogical changes, as well as the feasibility of the necessary accessibility for a truly inclusive practice. Thus, it must be considered that the Federal Network has developed inclusive actions, and sought to comply with educational legislation, but still needs to establish continuous inclusive processes for a successful and equitable training of the deaf student.
Keywords: federal education network; inclusive education; deaf student education